Preliminary study on dietary composition, feeding activity and fullness index of Boleophthalmus boddarti in Mekong delta, Vietnam - Quang, Dinh Minh (Academia Journal of Biology, 2015)
The mudskipper Boleophthalmus boddarti (Pallas, 1770) is an important commercial fish, but information on its dietary composition has been limited. This study was carried out from March 2013 to February 2014, in Tran De, Soc Trang, Mekong Delta, Vietnam to understand its food, foraging intensity and fullness index. A total of 120 fish specimens including 63 females (8-15 cm in TL) and 57 males (9.5-15.1 cm in TL) were collected and analysed. The results showed that the sex ratio of B. boddarti was close to 1:1 and this mudskipper would be a herbivorous fish due to high relative gut length value (RGL>1) based on 120 gastrointestinal tract length analysis. Among them, 75 fish stomachs were used for food item determination. The B. boddarti fed mainly on Bacillariophyta (82.97%), and detritus was also composed in its stomach contents (13.26%). The mudskipper showed high in foraging intensity due to high fullness index value. The variation of food composition of this fish depended on season, but not in gender and fish size. The results provided useful information on diet composition of B. boddarti and contributed to our knowledge for other gobies living in the monsoonal regions.